Endonuclease-based genotyping of the RBM as a method to track the emergence or evolution of SARS-CoV-2 variants - Eva Lopez (Elsevier, 2021)
Summary: Since the beginning of the COVID-19 pandemics, variants have emerged. Some of them display increased transmissibility and/or resistance to immune response. Most of the mutations involved in the functional adaptation are found in the receptor-binding motif (RBM), close to the interface with the receptor ACE2. We thus developed a fast molecular assay to detect mutations in the RBM coding sequence. After amplification, the amplicon is heat-denatured and hybridized with an amplicon of reference. The presence of a mutation can be detected using a mismatch-specific endonuclease and the cleavage pattern is analyzed by capillary electrophoresis. The method was validated on RNA of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants produced in vitro before being implemented for clinical samples. The assay showed 97.8% sensitivity and 97.8% specificity. The procedure can be set up for high-throughput identification of the presence of mutations and serve as a first-line screening to select the samples for full genome sequencing.